Anna Siwkowska, Proces inwestycyjno-budowlany dla instalacji OZE, seria Sektor Publiczny w Praktyce, Wydawnictwo C.H. Beck, Warszawa 2023, ss. 218, ISBN 978-83-8291-732-1 - Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2023)
Anna Siwkowska, Proces inwestycyjno-budowlany dla instalacji OZE, seria Sektor Publiczny w Praktyce, Wydawnictwo C.H. Beck, Warszawa 2023, ss. 218, ISBN 978-83-8291-732-1 (opr. Paulina Jachimowicz-Jankowska)